Reducing anxiety in pregnant women by prenatal gentle yo-ga - Armaita Armaita; Setia Nisa; Bella Lucintarillova; Yessi Aprihatin; Nibu R. Krishna; Alimuddin Alimuddin; Yovhandra Ockta; Rifqi Festiawan (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction and Objective: Pregnancy often brings both physical and psychological changes that can last throughout the nine months. Many pregnant women experience anxiety and fear about the labor process. Anxiety during pregnancy can lead to complications for both the mother and baby. Prenatal Gentle Yoga, a non-pharmacological treatment, has been suggested as a way to help pregnant women manage stress and anxiety, while preparing them mentally and physically for childbirth. The purpose of this study is to determine whether Prenatal Gentle Yoga can reduce anxiety levels in pregnant women in the third trimester, specifically primigravida women, in preparation for childbirth.